A Call to Action: The Needs of Breastfeeding Mothers on College and University Campuses. Issue 2 (March 2019) - Spatz, Diane L.
Abstract : Colleges and university campuses present a unique environment to meet the needs of breastfeeding women. Our breastfeeding expert, Dr. Spatz, offers an overview of how colleges and universities are helping faculty, staff, students, and campus visitors achieve their breastfeeding goals. She provides some suggestions for improvement.